The Impact of E-Procurement Management on Organizational Success: A Study of Lebanese Companies - CHARMAND, SIHAM (İstanbul Kültür Üniversitesi, 2025)
Procurement is becoming a strategic driver of company performance rather than a transactional role. Opportunities to enhance supplier management, cost control, and operational efficiency are presented by digital technology, particularly e-procurement platforms. However, regulatory pressures, a lack of digital maturity, infrastructure limitations, and unstable economic conditions make adoption extremely difficult for Lebanese SMEs. Through an analysis of organizational, technological, and environmental determinants, implementation problems, and managerial perceptions of results, this study explores the strategic influence of e-procurement adoption on SME performance in Lebanon. Five SMEs were examined using managerial interviews in 13 subject areas using qualitative cross-case analysis. The results show that stakeholder participation, strategy alignment, focused employee training, and organized supplier onboarding are essential for effective adoption. Operational sectors placed a higher priority on speed, accuracy, and usefulness, whereas regulated sectors placed a greater emphasis on compliance and transparency. Complete system integration and KPI tracking were essential to attaining quantifiable advantages, such as increased efficiency, compliance, and supplier dependability. SME managers looking to optimize technology, processes, and human resources in the face of difficult institutional and economic circumstances will benefit from the study's actionable insights and overall confirmation that strategic e-procurement adoption improves organizational performance.
Keywords: E-procurement; SMEs; Lebanon